1994
DOI: 10.1002/jhet.5570310120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of novel mitomycin C analogs derived from mitomycin A

Abstract: A variety of mitomycin C analogs were synthesized from mitomycin A and their biological activities were studied. Mitomycin A (1) underwent nucleophilic displacement reactions involving intramolecular hydrogen migrations upon treatment with nitrogen nucleophiles bearing mobile hydrogens, but the mode of hydrogen migration depended on the nature of the nucleophiles. The reaction with alkoxyamines gave compounds 6 and 7 which have the 5H‐6‐alkoxyimino‐4,7‐dione structure in ring A of 1. However, the reaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…1 One of the privileged substructures among the nitrogen-containing heterocycles is represented by the aziridine ring which has been found in a variety of biologically active natural products including mitomycin, azicemycin, azinomycin and maduropeptin. 2a,2b The structure-activity relationship (SAR) studies on mitosane derivatives revealed that the aziridine ring is crucial for their antitumor activity and selectivity. 2c–2f This study has led to the finding that mitomycin C can act as the most potent candidate possessing antitumor activities against stomach, breast, oesophagus and bladder tumors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 One of the privileged substructures among the nitrogen-containing heterocycles is represented by the aziridine ring which has been found in a variety of biologically active natural products including mitomycin, azicemycin, azinomycin and maduropeptin. 2a,2b The structure-activity relationship (SAR) studies on mitosane derivatives revealed that the aziridine ring is crucial for their antitumor activity and selectivity. 2c–2f This study has led to the finding that mitomycin C can act as the most potent candidate possessing antitumor activities against stomach, breast, oesophagus and bladder tumors.…”
Section: Introductionmentioning
confidence: 99%
“…2a,2b The structure-activity relationship (SAR) studies on mitosane derivatives revealed that the aziridine ring is crucial for their antitumor activity and selectivity. 2c–2f This study has led to the finding that mitomycin C can act as the most potent candidate possessing antitumor activities against stomach, breast, oesophagus and bladder tumors. 2b Many other aziridine-containing derivatives have also been found to exhibit various biological properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations